Baudelaire et Wagner - Landi, Michela (Biblioteca di Studi di Filologia Moderna, 2019)
Baudelaire et Wagner. "The intellectual name of love is interest", wrote Thomas Mann in his Considerations of an apolitical man (1915-1918). The interest, he specifies, "implies an emotional state that is nothing less than lukewarm", which "far exceeds in violence that of admiration'". It is not then in the panegyric, but in "malicious, even hateful" criticism, and in particular in the pamphlet (on condition "that it is spiritual and a product of passion") that this interest is found to be satisfied. The loving challenge that Thomas Mann issued at Wagner during the war is an answer, if possible, to Baudelaire's intention.